The gatekeeper images in hypertrophic cardiomyopathy: the role of native T1 mapping in Anderson-Fabry disease - Marzia Testa; Eleonora Indolfi; Guido Pastorini; Enrica Conte; Mauro Feola (Monaldi Archives for Chest Disease)
We presented a case of a 49-year-old presenting with atypical chest pain and hypertrophic phenotype cardiomyopathy without coronary artery disease. At cardiac magnetic resonance (CMR), the left ventricle was of normal volumes and preserved global ejection fraction with an asymmetric wall hypertrophy. The evaluation of native myocardial T1 has been calculated at an average global value of 924 ms, compatible with hypertrophic phenotype cardiomyopathy with reduced native T1 values as observed in Anderson-Fabry disease. The genetic analysis confirmed the Anderson-Fabry disease with a mutation in the exon 5 of the GLA gene, revealing the mutation c.644 A>G. This case report demonstrated that the images obtained in CMR and the analysis of the T1 native mapping, compared with the normal values obtained in the Center, may be considered a gatekeeper in the diagnostic assessment, avoiding redundant examinations, reducing costs, and radiological exposure.